2006
DOI: 10.3748/wjg.v12.i6.990
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscess associated with large colonic tubulovillous adenoma

Abstract: tract disease or intra-abdominal infections including cholecystitis, suppurative cholangitis, suppurative pylephlebitis, appendicitis, diverticulitis and peritonitis [1][2][3] . Recently, colorectal cancer without obvious infection was considered as one of the uncommon etiologies of liver abscess [4,5] . Furthermore, liver abscess was reported as the presenting manifestation of colonic tubulovillous adenoma [6] . However, there are a growing number of reports suggesting a relationship between diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…However, its association with tubullovillous adenomas has rarely been reported, with only one case published in the English literature 6. Here we present a case of a CLA possibly initiated by a tubullovillous adenoma in the colon.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, its association with tubullovillous adenomas has rarely been reported, with only one case published in the English literature 6. Here we present a case of a CLA possibly initiated by a tubullovillous adenoma in the colon.…”
Section: Introductionmentioning
confidence: 85%
“…Cryptogenic liver abscess (CLA) has been well recognised as the possible initial manifestation of a silent colorectal carcinoma 6 7. However, its association with tubullovillous adenomas has rarely been reported, with only one case published in the English literature 6.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the prevalence of advanced adenoma in this study (9.9%, 9/91 polyps) was also higher than that in general population (7.5%, 226/2,995 polyps) [29] despite limited statistical power due to small number of patients. It appears that PLA could develop at the stage of colonic adenoma [7,8]. Hence, an effort to detect adenomatous polyps in PLA patients is amply reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…PLA is associated with hepatobiliary tract disease or intra-abdominal infections [2]. In addition, PLA has been reportedly related to various colonic diseases, such as inflammatory bowel disease [3,4], diverticulitis [5,6], colonic adenoma [7,8], and colorectal cancer (CRC) [9,10,11,12,13,14,15]. The term ‘cryptogenic PLA' is used when a significant underlying cause of PLA cannot be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports assert that cryptogenic PLA might be a presentation of occult or silent colorectal cancer or adenoma without any gastrointestinal symptoms on admission (5, 7, 8, 14). Studies by Cohen et al (6), Nosher et al (28) and Yeh et al (29) revealed that 5% (1/20 patients), 6.7% (1/15 patients) and 11.5% (6/52 patients) of patients with PLA had colorectal cancer respectively.…”
Section: Discussionmentioning
confidence: 99%